LINC00472 suppressed by ZEB1 regulates the miR‐23a‐3p/FOXO3/BID axis to inhibit the progression of pancreatic cancer. Issue 17 (7th August 2021) - Bi, Cong; Wang, Gang
Abstract: The tumour‐suppressive role of LINC00472 has been extensively reported in various human cancers such as lung, colon and ovarian cancers, yet its function in pancreatic cancer remains unidentified. Here, the current research aimed to explore the role and regulatory axis mediated by LINC00472 in the progression of pancreatic cancer. RT‐qPCR was adopted to determine LINC00472 expression in the harvested pancreatic cancer tissues and adjacent normal tissues. Loss‐of‐function and gain‐of‐function experiments were performed to examine the effects of LINC00472 on proliferation and apoptosis in vitro and tumorigenesis in vivo. Immunoblotting was performed to detect the expression of several proliferation and apoptosis‐related proteins. Bioinformatic analysis, dual‐luciferase reporter assay and RNA pull‐down were conducted to profile the relationships between LINC00472 and miR‐23a‐3p, between miR‐23a‐3p and FOXO3 and between FOXO3 and BID. The LINC00472 expression was down‐regulated by ZEB1 in the pancreatic cancer cells and tissues. LINC00472 could competitively bind to miR‐23a‐3p to enhance the expression of FOXO3, which consequently could promote the BID expression, thereby suppressing proliferation and promoting the apoptosis of pancreatic cancer cells. Meanwhile, the inhibitory role of LINC00472 in tumorigenesis was validated in vivo, and the LINC00472‐mediated miR‐23a‐3p/FOXO3/BID axis was also demonstrated in the nude mouse tumour formation model. The study substantiated the antitumour activity of LINC00472 in pancreatic cancer and proposed a regulatory axis in which LINC00472 competitively binds to miR‐23a‐3p to enhance the FOXO3 expression and promote BID expression. Consequently, these findings provide theoretical basis for developing potential targets for the treatment of pancreatic cancer.